Direct measurement of the male germline mutation rate in individuals using sequential sperm samples - Jonathan E. Shoag; Amoolya Srinivasa; Caitlin A. Loh; Mei Hong Liu; Emilie Lassen; Shana Melanaphy; Benjamin M. Costa; Marta Grońska-Pęski; Nisrine T. Jabara; Shany Picciotto; Una Choi; Anyull D. Bohorquez; et al. (Nature Communications)
Abstract Mutations that accumulate in the human male germline with age are a major driver of genetic diversity and contribute to genetic diseases. However, aging-related male germline mutation rates have not been measured directly in germline cells (sperm) at the level of individuals. We developed a study design in which we recalled 23 sperm donors with prior banked samples to provide new sperm samples. The old and new sequential sperm samples were separated by long timespans, ranging from 10 to 33 years. We profiled these samples by high-fidelity duplex sequencing and demonstrate that direct high-fidelity sequencing of sperm yields cohort-wide mutation rates and patterns consistent with prior family-based (trio) studies. In every individual, we detected an increase in sperm mutation burden between the two sequential samples, yielding individual-specific measurements of germline mutation rate. Deep whole-genome sequencing of sequential sperm samples from two individuals followed by targeted validation measured remarkably stable mosaicism of clonal mutations that likely arose during embryonic and germline development, suggesting that age did not substantially impact the diversity of spermatogonial stem cell pools in these individuals. Our application of high-fidelity and deep whole-genome sequencing to sequential sperm samples provides insight into aging-related mutation processes in the male germline.